Intra-annual climate variability and malaria transmission in Nigeria - Ayanlade, Ayansina; Adeoye, Nathaniel Olugbade; Babatimehin, Oyekanmi (Bulletin of Geography. Socio-economic Series, 2013)
This study develops an integrated innovation for malaria early warning systems (MEWS), based on vulnerability monitoring, seasonal climate variability data, and epidemiologic surveillance. The main aim of the study is to examine the relationship between intra-annual climate variability and malaria transmission in Nigeria. For this study, climatic conditions considered suitable for the development of the malaria parasite and its transmission through the mosquito stage of its life cycle are temperatures within the range from 18°C to 32°C. Below 18°C the parasite development decreases significantly, while above 32°C the survival of the mosquito is compromised. Relative humidity greater than 60% is also considered a requirement for the mosquito to survive long enough for the parasite to develop sufficiently to be transmitted to its human host stage. The research findings show that seasonality of climate greatly influences the seasonality of malaria transmission. Specifically, rainfall plays an important role in the distribution and maintenance of breeding sites for the mosquito vector. Rainfall and surface water is required for the egg laying and larval stages of the mosquito life cycle and monthly rainfall above 80 mm is considered a requirement. Also, it is temperature that regulates the development rate of both the mosquito larvae and the malaria parasite (Plasmodium species) within the mosquito host. Relative humidity and temperature play an important role in the survival and longevity of the mosquito vector. This study is in conformity with the findings of the IPCC (2001) that malaria is caused by four distinct species of the Plasmodium parasite, transmitted by mosquitoes of the genus Anopheles, which are most abundant in tropical/subtropical regions, although they are also found in limited numbers in temperate climates.